1999
DOI: 10.1111/j.1095-8649.1999.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Papyrus swamps, hypoxia, and faunal diversification: variation among populations of Barbus neumayeri

Abstract: To test whether patches of papyrus swamp contribute to diversification of populations of non-air-breathing fishes, the gill morphology of Barbus neumayeri was compared between a papyrus swamp and several tributaries which differed in oxygen regime. Total gill filament length differed among sites and was negatively related to dissolved oxygen availability, supporting strong selection pressure for low-oxygen tolerance in the swamp interior. Among recaptures of marked B. neumayeri over a 4·5-year period among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 48 publications
5
70
0
Order By: Relevance
“…TGSA was one such trait (Fig. 4), consistent with the crucial role of the gills in oxygen uptake, as well as previous observations that the capacity of the gills for gas exchange increases in response to hypoxia exposure (Chapman et al, 1999;Sollid et al, 2003) and is greater in fish with greater hypoxia tolerance (Mandic et al, 2009). Larger gills are also characteristic of the high performance tunas and lamnid sharks (Bernal et al, 2001).…”
Section: Traits Underlying Both Hypoxia Tolerance and Exercise Perforsupporting
confidence: 57%
“…TGSA was one such trait (Fig. 4), consistent with the crucial role of the gills in oxygen uptake, as well as previous observations that the capacity of the gills for gas exchange increases in response to hypoxia exposure (Chapman et al, 1999;Sollid et al, 2003) and is greater in fish with greater hypoxia tolerance (Mandic et al, 2009). Larger gills are also characteristic of the high performance tunas and lamnid sharks (Bernal et al, 2001).…”
Section: Traits Underlying Both Hypoxia Tolerance and Exercise Perforsupporting
confidence: 57%
“…In Barbus neumayeri, genetic differentiation among sampling sites that presented different oxygen rates could represent the effects of selective pressure (Chapman et al, 1999). The well-developed homing instinct of salmonid fish seems to be a decisive factor leading to strong population subdivisions (Ryman, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the adaptation to lifelong hypoxia is mainly due to improved oxygen transport. Some species like B. neumayeri survived extreme hypoxic conditions in the wetlands by combination of low metabolism, high haemoglobin, and very efficient use of aquatic surface respiration (Chapman & Liem, 1995;Olowo & Chapman, 1996;Chapman et al, 1999).…”
Section: Haemoglobin Switchingmentioning
confidence: 99%